2011
DOI: 10.1017/jfm.2011.422
|View full text |Cite
|
Sign up to set email alerts
|

Flow instabilities between two parallel planes semi-obstructed by an easily penetrable porous medium

Abstract: A study of instabilities in planar flows produced by the presence of a parallel penetrable porous obstruction is presented. The case considered is a flow between parallel plates partially obstructed by a porous medium. The most unstable perturbation modes are obtained solving numerically the eigenvalue problem derived from the linear stability analysis of the two-dimensional Navier-Stokes equations applied to the geometry of interest. The analysis leads to an extended Orr-Sommerfeld equation including a porous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
3
7
0
4
Order By: Relevance
“…Del cálculo de estabilidad lineal se obtuvieron los números de Reynolds críticos (Re h =ρh 3 /8µ 2 (-dp/dx) [7]), resultando 90 para el canal asimétrico y 71 para el simétrico. A continuación se presentan resultados numéricos y experimentales para casos subcríticos y supercríticos.…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Del cálculo de estabilidad lineal se obtuvieron los números de Reynolds críticos (Re h =ρh 3 /8µ 2 (-dp/dx) [7]), resultando 90 para el canal asimétrico y 71 para el simétrico. A continuación se presentan resultados numéricos y experimentales para casos subcríticos y supercríticos.…”
Section: Resultsunclassified
“…al. [7]. De esta forma se obtiene una ecuación diferencial ordinaria de cuarto orden muy similar a la ecuación de Orr-Sommerfeld pero con un término adicional que representa la amortiguación introducida por el medio poroso.…”
Section: Método Experimentalunclassified
See 2 more Smart Citations
“…Interestingly, the theoretical results reported by Socio et al [14] shows no bi-or tri-modal behavior in the neutral stability curve. The experimental data obtained by Silin et al [15] also showed no sign of bi-modal stability curve. Tilton and Cortelezzi [16] argued that the prediction of bi-and tri-modal neutral stability curves in Refs.…”
Section: Introductionmentioning
confidence: 85%